Analysis of Influence Style Leadership, Motivation, and Work Environment on Employee Performance PT. Bank Capital Indonesia, Tbk - Eva Nopalina Panjaitan; Meita Pragiwani (Indonesian Journal of Business, Accounting and Management (IJBAM), 2019)
This study aims to determine the influence of leadership style, motivation, and work environment on the performance of employees of PT. Bank Capital Indonesia (Operational Head Office). The method used in the preparation of this thesis is to use a causal associative method. Causal associative research is a study that aims to determine the effect between two or more variables. This research explains the influence and influence relationship of the variables to be studied. The object of this research is employees at PT. Bank Capital Indonesia, Tbk Operational Headquarters, where the author distributes a written questionnaire to be given to employees of PT. Bank Capital Indonesia, Tbk Operational Headquarters to be answered using the "Likert Scale". In this study was taken 150 employees as respondents in March 2017. Data analysis tool used in this study is multiple linear regression analysis. From result of research known that there is significant influence between leadership style, motivation, and work environment to employee performance. From 3 (three) research variables analyzed, that motivation variable is the most dominant variable affecting employee performance and followed by work environment variable and leadership style variable.